KETERLAMBATAN MAHASISWA DALAM STUDI DITINJAU DARI TEORI ATRIBUSI DARI WEINER - Yuli Darwati (IAIN Kediri, 2015)
This study is aims at finding some causes why some students became slow learners by employing the attribution theory proposed by Weiner.Regarding to Weiner’s theory, the researcher finds that slow learning among studens is strongly related to their attribution toward the success and failure during learning process. That is the reason why slow learning is likely to happen. Such cases happen when the students attribute their success and failure in learning based on external and internal factors so that stability and unstability are controallable. When the success is attributed by the external and internal factors and stability, the possibility to get success in the future is likely to happen again and the satisfation overwhelms the student. On the other hand, when the students fail during learning, it will make them to be embarrassed, to lose their dignity and to have negative assumption toward the failure in the future. In addition, the repeatly failure among the students might cause a phenomena which is commonly called learning helplessness. Learning helplessness make the students not only to be a slow learner but also not to be able to complete the study.Key Words: Attribution, success, failure, external or internal, stability, learning helplessness.